Pemenuhan Hak Atas Pendidikan bagi Anak-anak Pengungsi di ASEAN dengan Memperkuat Prinsip ASEAN - Rachminawati Rachminawati; Stevanus Aditya Kebingin (Faculty of Law, Maranatha Christian University, 2023)
The right to education for refugees, particularly child refugees, is seen as a fundamental right. According to data from the United Nations High Commissioner for Refugees (UNHCR), nearly half of all child refugees have had no official or informal schooling. The realization of the right to education in the Association of Southeast Asian Nations (ASEAN) region presents unique problems, particularly for refugee children from Myanmar's Rakhine State. The ASEAN Ways are often being claimed as the main hindrance in tackling the problem. However, to some extent, it has proven in maintaining stability in the ASEAN region. This paper examines how ASEAN Ways approach fulfilling the right to education in terms of policy and implementation through the Bali Process consensus and relevant ASEAN organs such as the ASEAN Intergovernmental Commission on Human Rights (AICHR) and ASEAN organizations in education cooperation (SEAMEO). The legal and qualitative research methods have been used in this study. As the outcome, this study shows that the ASEAN Ways approach in protecting the right to education especially for refugee children from Rakhine states provides a stronger foundation for fulfilling their rights in each of ASEAN destination countries such as Indonesia, Malaysia, Philippines, and Thailand. Although national laws and regulations differ from one state to the next, it will promote the fulfillment of the right to education while sustaining stability in the ASEAN region with support from ASEAN as a regional organization via reinforcing the principles of ASEAN Ways.